Food insecurity: special considerations for women(1)(2)(3)(4) - Ivers, Louise C (American Society for Nutrition, 2011)
Food security exists when all people, at all times, have physical, social, and economic access to sufficient, safe, and nutritious food that meets their dietary needs and food preferences for an active and healthy life. Food insecurity is the converse state, is often associated with poverty and low income, and has important implications for the health and nutrition of individuals. Given their contribution to food production and preparation, their role in society as child bearers and caregivers, the increasing number of female-headed households worldwide, and their disproportionately poor economic status, women need special consideration in discussions of food insecurity and its effect on health, nutrition, and behavior. This article reviews the scientific literature on issues related to women and food insecurity. Food insecurity is associated with obesity, anxiety, and depressive symptoms; risky sexual behavior; poor coping strategies; and negative pregnancy outcomes in women, although evidence about the direction and causality of associations is unclear. There is a lack of evidence and understanding of the effects of food insecurity in resource-poor settings, including its effect on weight, nutritional outcomes, and pregnancy outcomes, as well as its effect on progression of diseases such as HIV infection. More research is needed to guide efficient interventions that address food insecurity among women. However, practical experience suggests that both short-term assistance and longer-term strategies that improve livelihoods, address behavioral and coping strategies, acknowledge the mental health components of food insecurity, and attempt to ensure that women have the same economic opportunities, access to land, and economic power as men are important.